Advances in nanocomposites-based electrochemical biosensors for the early diagnosis of breast cancer - Gamal, Osman; Eldin, Mariam Hossam; Refaat, Aya A.; Hassan, Rabeay Y. A. (Frontiers in Sensors, 2024)
Regardless of many years of research work and conducting numerous clinical studies, breast cancer (BC) continues to grow among women, threatening their lives and future. Currently, it affects more than 10 % of women globally. Therefore, researchers have recently redirected their endeavors toward detecting BC at an early stage, recognizing its substantial impact on survival rates, and acknowledging its immense potential for providing effective cancer treatments at this early diagnosed disease stage. The utilization of biomarker-based diagnostic techniques significantly contributes to the advancement of early detection and precision. A wide range of biomarkers is linked to every newly diagnosed BC case. Traditionally, breast cancer was diagnosed using a variety of techniques such as mammography, molecular imaging, and ultrasonography. These techniques had several drawbacks, drawing the attention of many scientists to developing new methods and strategies. Among these strategies, electrochemical biosensors have proven to be excellent alternatives to more complex and traditional detection strategies in terms of performance, accuracy, robustness, and a tremendous range of applications. In this review, the use of conventional methods for detecting BC as well as their challenges and shortcomings have been stated. Moreover, a deep discussion was given to the newly developed nanocomposite-based electrochemical bio-sensing approaches that have been exploited for the effective detection and quantification of breast cancer biomarkers.